Cold Application on Bruising at the Subcutaneous Heparin Injection Site: A Systematic Review and Meta-Analysis - Sara Amaniyan MScN, BScN; Akram Ghobadi MScN, BScN; Mojtaba Vaismoradi PhD, MScN, BScN (SAGE Publishing, 2020)
Abstract Despite the documented clinical efficacy, the injection of subcutaneous heparin can be associated with adverse drug reactions including bruising at the injection site. This study sought to systematically assess current evidence regarding the effect of cold application as a fundamental nursing intervention on the occurrence and size of bruising at the injection site in patients receiving subcutaneous heparin. A systematic review and meta-analysis of randomized controlled trials and quasi-experimental studies was performed. Web of Knowledge, PubMed (including MEDLINE), Scopus, Embase, Cochrane library, gray literature, and cross‐referencing from reference lists were searched from 2000 to 2019. Quality of selected studies was assessed using the Cochrane risk of bias appraisal tool for randomized controlled trials and the JBI MASTARI appraisal tool for quasi-experimental studies. The search yielded 3,220 articles, but consideration of inclusion criteria led to final selection of 9 articles. The meta-analysis showed that cold application significantly reduced the relative occurrence of bruising at the subcutaneous heparin injection site by 40% (relative risk, 0.60; 95% confidence interval [0.39, 0.91]) and reduced the bruising size (standardized mean difference, −2.78; 95% confidence interval [−4.34, −1.22]). Cold application as a fundamental nursing intervention can be an effective intervention to prevent adverse drug reactions at the injection site in terms of the occurrence and size of bruising in patients receiving subcutaneous heparin.